2023
DOI: 10.3390/agronomy13010250
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Effect of Cutting Angle on the Growth of Grafted Watermelon Seedlings Using the One-Cotyledon Grafting Method

Abstract: The labor-efficient automation of grafting has been recognized as a key factor in the wider adoption of grafting. In growing cucurbits, the root pruned one-cotyledon grafting method is the most commonly used method with grafting machines. The cutting angle, which affects the matching of the rootstock and scion, is key to the survival of the graft seedling. In the production of cucurbit graft seedlings, the cutting parameters are established based on experience, leading to low grafting success. To determine acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore, increasing the area of the healing contact surface of the rootstock and scion can improve the healing survival rate of grafted seedlings, which is generally measured by the length of the cut surface [19]. Liang et al analyzed the effect of different cutting angles (14 • , 17 • , and 27 • ) on the healing and survival of grafted seedlings from an agronomic point of view and found that smaller cutting angles were more favorable for grafting survival [26]. These results are similar to the results of the present study, where the length of the cut surface was longer for smaller cutting angles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increasing the area of the healing contact surface of the rootstock and scion can improve the healing survival rate of grafted seedlings, which is generally measured by the length of the cut surface [19]. Liang et al analyzed the effect of different cutting angles (14 • , 17 • , and 27 • ) on the healing and survival of grafted seedlings from an agronomic point of view and found that smaller cutting angles were more favorable for grafting survival [26]. These results are similar to the results of the present study, where the length of the cut surface was longer for smaller cutting angles.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al investigated the effects of three cutting angles (14 • , 17 • , and 27 • ) of melon rootstock seedlings on the healing survival and later growth of grafted seedlings. The results showed that the smaller the cutting angle, the earlier the phloem reattachment occurs, and the greater the tensile strength of the scion-rootstock union during the healing period, the more favorable the grafted seedling survival rate [26]. The study did not consider the interaction of cutting angle with cut quality and cutting success, which need to be taken into account in the actual cutting process.…”
Section: Introductionmentioning
confidence: 98%
“…For optimal rootstock grafting, the seedling age was set at 8 to 10 days, with the external morphology of the rootstock characterized by two spreading cotyledons and a stem thickness of about 3.5 mm, as depicted in Figure 14a. In contrast, the scion was sown three days earlier than the rootstock, displaying 2 to 3 leaves in its growth [39,40], as shown in Figure 14b. The designed spray grafting device was subjected to drawing, machining, module assembly, and control software development to integrate the spray grafting device as shown in Figure A5, which only requires one person to operate it.…”
Section: Tests 221 Test Materialsmentioning
confidence: 99%
“…Among cucurbit growers, the root pruned one-cotyledon grafting method, combined with the use of grafting machines, is the most commonly employed approach. However, success in grafting is not solely dependent on the use of machines; the cutting angle, which determines the compatibility of the rootstock and scion, plays a vital role in the survival and growth of the grafted seedling [27]. For example, Sun et al [37] explored the broken head rate and stubble break rate of potato seedlings by the automatic machine for cutting and raising potato seedlings.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the method of producing seedlings from cuttings can make the plant growth speed very rapid. Compared with other seedling methods such as seeding, cuttings have better genetics and better survival rates [27]. Seedling production from cuttings must be provided with specific temperature, humidity, and photosynthetic active radiation (PAR) requirements.…”
Section: Introductionmentioning
confidence: 99%